Viabilidade econômica e financeira para implantação de Centro Estético na cidade de Presidente Prudente - SP - PEREIRA, Anderson da Rocha; CHIZZOLINI, Nicolas Domingos (157, 2024)
A presente pesquisa teve como objetivo avaliar a viabilidade econômica e financeira da implantação de centro estético na cidade de Presidente Prudente, SP. A pesquisa se baseou na análise de um plano de negócios que incluiu estudo de mercado, análise de concorrência, estratégias de marketing, planejamento financeiro e projeções de lucro. A proposta enfatizou a inovação do produto e a criação de um ambiente diferenciado como vantagens competitivas, considerando também a exclusividade do produto no mercado local. O estudo apontou que o empreendimento, denominado Giovana Cellis Beauty, tem potencial para atender à demanda regional e se destacar no setor da beleza, especialmente pela oferta de produtos exclusivos e uma experiência única e inovadora. O plano prevê estratégias de marketing voltadas para o público jovem ao de meia idade, além de um enfoque em parcerias estratégicas com fornecedores, social media e influencers, assim como o uso de tecnologias para otimização do serviço. Concluiu-se que, com uma gestão eficiente e estratégias de crescimento bem delineadas, o empreendimento apresenta uma alta probabilidade de sucesso, podendo se consolidar como uma referência na cidade e expandir no futuro.

The objective of this research was to evaluate the economic and financial feasibility of establishing an aesthetic center in the city of Presidente Prudente, SP. The research was based on the analysis of a business plan that included a market study, competition analysis, marketing strategies, financial planning, and profit projections. The methodology used was mixed, encompassing quantitative research with financial simulations and secondary data analysis, as well as qualitative research through content analysis of documentary sources and a literature review. The proposal emphasized product innovation and the creation of a differentiated environment as competitive advantages, also considering the exclusivity of the product in the local market. The study indicated that the enterprise, named Giovana Cellis Beauty, has the potential to meet regional demand and stand out in the beauty sector, especially by offering exclusive products and a unique and innovative experience. The plan includes marketing strategies aimed at a young to middle-aged audience, as well as a focus on strategic partnerships with suppliers, social media, and influencers, along with the use of technologies to optimize service. It was concluded that with efficient management and well-defined growth strategies, the venture presents a high probability of success and could establish itself as a reference in the city and expand in the future.
Economic and financial viability for the implementation of a Beauty Center in the city of Presidente Prudente – SP
Keywords: Gestão de negócios; Inovação; Empreendedorismo; Gestão e Negócios